WADAH KERAJINAN TANGAN MAKANAN DAN MINUMAN DI JUANDA - Marvel Buhamir; Budi Adelar Sukada (Jurusan Arsitektur dan Perencanaan, 2020)
Cities are centers of settlements and activities of residents who have administrative boundaries that are regulated in laws and regulations as well as settlements that have displayed the character and characteristics of urban life. Humans also needs of daily life. And also humanity has its own family, then each human being also needs an economy to maintain human life. In everyday human needs the main staple, namely eating to revive humans. And also some people need pleasure, enjoyment, such as releasing negative things like faith, natural disturbances and so on. In this research, humans always think about life, namely hunger to eat something for human life. Also there are also some food and beverage sales such as restaurants, kiosks, supermarkets, markets and so on. So humans also daily activities will definitely go to a place that needs daily life. And also want to follow to make something creative. In logic, today many young people often hang out at coffee shops and also only order coffee and chat with other people. Well so this must also provide to know the process of food and drink, even the public also wants to bring happiness and pleasure. Food and beverage handicrafts are for the people. Providing buildings that we plan to craft food and drinks on the premises for the community. Being a food and beverage craftsman is an innate happiness and pleasure for the community, that is social justice for all people respectively. Example of food: Bread that is cut into pieces to form animals or caricatures themselves. As well as examples of drinks: coffee drinks have their own consumer photos on it. So this is a place where the transfer of something new is a third place for the community, we plan this for a business startup or popularly called a stub. Keywords: architecture; drinks; food; humanity; lifeprocesses AbstrakKota adalah pusat permukiman dan kegiatan penduduk yang mempunyai batas wilayah administrasi yang diatur dalam peraturan perundang-undangan. Manusia sebagai warga kota membutuhkan pemenuhan kebutuhan kehidupan sehari-hari. Dalam upaya pemenuhan kebutuhan sehari-hari, manusia membutuhkan makanan sebagai kebutuhan utama. Selain makanan, manusia juga memiliki kebutuhan akan kesenangan, kenikmatan, seperti melepaskan dari hal-hal negatif seperti stress dsb. Studi ini bertujuan untuk memikirkan tentang bagaimana aktivitas mencari makanan menjadi sesuatu yang menarik dan dikolaborasikan dengan aktivitas lainnya. Dimana proses mencari makanan dan minuman pun seyogyanya membawa kebahagiaan dan kesenangan. Kerajinan tangan makanan dan minuman menjadi sebuah usulan proyek dan terobosan baru bagi masyarakat. Program dan aktivitas untuk kerajinan tangan makanan dan minuman, pengrajin makanan dan minuman itu merupakan bawaan kebahagiaan dan kesenangan untuk masyarakat. Proyek diharapkan menjadi sebuah tempat yang perpindahan sesuatu yang baru merupakan third place bagi masyarakat, Kami rencanakan ini untuk sebuah rintisan bisnis atau populer disebut start up.